THE IMPACT OF ADULT SONG ON THE SOCIAL-EMOTIONAL DEVELOPMENT OF CHILDREN AGED 5-6 YEARS AT KARTIKA IV-73 KINDERGARTEN IN JEMBER - Syifa, Syifa Kartika Putri; Aisiyah, Laily Nur; Atika, Aisyah Nur (PG PAUD Universitas Negeri Surabaya, 2024)
The advancement of technology has changed the way we access entertainment, including adult songs that quickly become popular. Young children easily access such content, impacting their growth and development, as adult songs often touch on themes like romance and infidelity. At Kartika Kindergarten IV-73 Jember, some children enjoy singing adult songs they find on social media platforms such as YouTube and TikTok. This research aims to describe the impact of adult songs on the social-emotional development of 5-6 year-old children at Kartika Kindergarten IV-73 Jember. The research method used is qualitative with a descriptive approach, employing data collection techniques such as interviews, observations, and documentation. The research results show both positive and negative impacts. Positively, there's better emotional expression in children. However, there are negative impacts due to exposure to violent content, which can trigger aggressive behavior and difficulties in managing emotions. Media influence can also alter perceptions and behaviors related to social relationships and love, including difficulty in adhering to rules and displaying less disciplined behavior. Nonetheless, children still demonstrate attitudes of sharing, competition, and empathy in interactions with peers. In conclusion, it's crucial for adults to monitor children's access to media content, especially adult songs, to minimize negative impacts and support their positive development